2011
DOI: 10.3109/07434618.2011.577449
|View full text |Cite
|
Sign up to set email alerts
|

“He Cares About Me and I Care About Him.” Children's Experiences of Friendship with Peers who use AAC

Abstract: Typically developing children face multiple challenges in developing friendships with peers who have severe physical disabilities and use augmentative and alternative communication (AAC), especially when these peers experience restrictions in mobility, educational participation, physical access, and communication. In this small qualitative study, six typically developing children were interviewed about their friendships with classmates who have cerebral palsy and use AAC. Data were analyzed according to Riessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 23 publications
11
63
0
Order By: Relevance
“…In many respects, parents and children described issues similar to those reported by other researchers, including: (a) limited locations for activity engagement outside of school and home Thirumanickam et al, 2011), (b) limited contact and interactions with peers (Bailey et al, 2006;Clarke & Kirton, 2003), (c) slow pace of communication (Smith, 2005;von Tetzchner & Martinsen, 2000), (d) communication partners dominating interactions (Kent-Walsh & McNaughton, 2005;von Tetzchner & Martinsen, 1996, 2000, (e) frequent technology breakdowns (Shepherd, Campbell, Renzoni, & Sloan, 2009), and (f) lack of close relationships with peers (Anderson et al, 2011;Raghavendra et al, 2012). However, this study provides a unique account of children ' s and parents ' perceptions of these issues as they relate to children ' s social participation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In many respects, parents and children described issues similar to those reported by other researchers, including: (a) limited locations for activity engagement outside of school and home Thirumanickam et al, 2011), (b) limited contact and interactions with peers (Bailey et al, 2006;Clarke & Kirton, 2003), (c) slow pace of communication (Smith, 2005;von Tetzchner & Martinsen, 2000), (d) communication partners dominating interactions (Kent-Walsh & McNaughton, 2005;von Tetzchner & Martinsen, 1996, 2000, (e) frequent technology breakdowns (Shepherd, Campbell, Renzoni, & Sloan, 2009), and (f) lack of close relationships with peers (Anderson et al, 2011;Raghavendra et al, 2012). However, this study provides a unique account of children ' s and parents ' perceptions of these issues as they relate to children ' s social participation.…”
Section: Discussionsupporting
confidence: 76%
“…This suggests that they may lack experiences with peers that provide a sense of loyalty and commitment and lead to closeness or intimacy, which typically characterize friendships of children and youth without disabilities (Doll, 1996). This is similar to the fi ndings from other studies indicating that children who use AAC tend to rely on adults rather than peers for emotional support and that the friendships of children and adolescents who use communication aids lack depth (Anderson et al, 2011). Anderson and colleagues suggested that friendships between children using communication aids and children with natural speech may be more asymmetric than those between children with natural speech, because the former are more likely to include helping relationships.…”
Section: Social Relationshipssupporting
confidence: 77%
“…Light, Arnold, and Clark (2003) identifi ed a range of sociorelational skills that may further the communicative competence of individuals who use AAC (e.g., participating actively in interactions, demonstrating interest in partners, projecting a positive self image). Sociorelational skills bear special importance for individuals with complex communication needs who may face signifi cant barriers to interpersonal relationships (Anderson, Balandin, & Clendon, 2011;Light et al, 2003). Jim Prentice, an expert communicator via AAC who worked as a statistical record keeper at a large company, poignantly illustrated the importance of developing social competence:…”
Section: Adequacy Of Communicationmentioning
confidence: 99%
“…Now, many individuals who use AAC expect to be full participants in a wide range of environments -family, school, work, and community (McNaughton & Kennedy, 2010). Children with cerebral palsy, ASD, Down syndrome, and other developmental disabilities are using AAC to participate in general education classrooms, to learn literacy skills, and to interact with friends and family members (e.g., Anderson, Balandin, & Clendon, 2011;Light & McNaughton, 2009Kent-Walsh & Light, 2003;Finke, McNaughton, & Drager, 2009;Stoner, Angell, & Bailey, 2010). Adults with severe disabilities are living in the community and using AAC to participate in employment, to volunteer, and to take part in recreational activities (e.g., McKelvey et al, 2012;McNaughton, Light, & Arnold, 2002;McNaughton, Light, & groszyk, 2001;Dattilo, Estrella, Estrella, Light, McNaughton, & Seabury, 2008;Trembath et al, 2010).…”
Section: Changes In Expectations For Participation and Inclusionmentioning
confidence: 99%